Minimum wage regulation in Switzerland: Survey evidence for restaurants in the canton of Neuchâtel - Marius Berger; Bruno Lanz (Swiss Journal of Economics and Statistics, 2020)
This paper provides a first set of results on the impact of minimum wage regulation in Switzerland. We study the effects of an unexpected Supreme Court ruling mandating the Swiss canton of Neuchâtel to enforce a minimum hourly wage of around CHF 20 previously accepted via popular ballot. Given policy discontinuity at cantonal borders, we design a two-wave survey of restaurants to measure wages, employment, workers' characteristics, and prices and administer it in Neuchâtel as well as in geographically proximate districts of neighboring cantons. Our data covers pre- and post-enforcement outcomes for around 100 restaurants, with information for more than 800 employees distributed over two-survey waves. Our data suggest that the proportion of workers paid below minimum wage went down from 19% to 5% after the introduction of the policy. This decline is compensated by a significant increase of the workforce paid just above minimum wage, and our results suggest that restaurants did not use employment as a margin of adjustment. We also find evidence that the policy affected the distribution of hourly wages up to CHF 6 above the minimum wage, with some workers initially paid above minimum wage experiencing a wage increase.
Keywords: J21; J23; J38; C83; R23; 330; Minimum wage regulation; Wage distribution; Workforce composition; Low-wage jobs; Restaurant industry